ANALYSIS OF MAIN CHARACTERS IN BEAUTY AND THE BEAST MOVIE BY JOHN ALVIN - Laras Wahyu Kinanti; Bambang Eko Siagiyanto; Aulia Hanifah Qomar (Journal of English Education and Enterpreneurship (JEEP), 2022)
The research discusses about main characters in “Beauty and The Beast” Movie. Maincharacters is the figure whose story is prioritized in a literary work in question. Because thatis the most widely told character, both as the perpetrators of events and those subject toevents. The objectives of this research are to know kind of characters in beauty and the beastmovie and to explain how are the main characters described. Character in movie is the objectof this research. The main character is the subject of this research. The method of thisresearch is Descriptive Qualitative research. The result of this study are found 6 kind of characters, 2 main characters and 10characters. Kind of characters consist of protagonist, antagonist, dynamic, round, static andflat were 13 data, main characters consist of Belle and the beast and characters consist ofhumble, friendly, curious, helpful, loving, brave, struggle, angry, arrogant and feel guilty were10 data. Based on the data it can be concluded that in beauty and the beast movie only found6 kind of character and 10 characters except main characters only 2 are analyzed.